2012
DOI: 10.1111/j.1365-2672.2012.05238.x
|View full text |Cite
|
Sign up to set email alerts
|

DnaK and GroEL chaperones are recruited to the Bacillus subtilis membrane after short-term ethanol stress

Abstract: Aims:  To find out membrane tolerance strategy to ethanol in Bacillus subtilis that possesses a powerful system of protection against environmental stresses. Methods and Results:  Cytoplasmic membranes of B. subtilis were severely affected by even short‐term exposure to 3% (v/v) ethanol: the growth rate and membrane protein synthesis were markedly reduced, and no adaptive alterations in phospholipids were detected. Simultaneously, steady‐state DPH fluorescence anisotropy (rss) showed that the membrane rigidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 44 publications
(70 reference statements)
2
32
0
1
Order By: Relevance
“…Ethanol increases membrane leakage and affects the properties of all biological molecules in bacteria (6,26). In B. subtilis, ethanol induces recruitment of the molecular chaperones DnaK and GroEL to the cell membrane (52). Interestingly, the DEAD-box RNA helicase CrhR of the cyanobacterium Synechocystis sp.…”
Section: Resultsmentioning
confidence: 99%
“…Ethanol increases membrane leakage and affects the properties of all biological molecules in bacteria (6,26). In B. subtilis, ethanol induces recruitment of the molecular chaperones DnaK and GroEL to the cell membrane (52). Interestingly, the DEAD-box RNA helicase CrhR of the cyanobacterium Synechocystis sp.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the phospholipid composition of the L. lactis membrane which is composed of saturated, unsaturated, and cyclic fatty acids (37), similar to the O. oeni membrane. In contrast, the B. subtilis membrane has a high saturated fatty acid content (90%) (11). Phospholipid composition also influences the degree to which temperature affects the lipid organization (termed "lipid bilayer phase behavior").…”
Section: Discussionmentioning
confidence: 99%
“…The stabilizing effect of Lo18 on other natural membranes was checked by using liposomes made from phospholipids extracted from B. subtilis or L. lactis. These two bacteria have a fatty acid content distinct from that of O. oeni (11,37). B. subtilis contains predominantly branched saturated fatty acids, leading to a membrane of higher rigidity (R ϭ 0.191 units) than O. oeni (R ϭ 0.163) and L. lactis (R ϭ 0.177).…”
Section: Interaction Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Bukau et al (1993) showed the presence of DnaK on the membrane of E. coli, as detected by electron microscopy, an observation that has been forgotten for many years. The presence of DnaK in membranes has also been reported in Fusobacterium nucleatum (Skar et al 2003) and Bacillus subtilis (Seydlova et al 2012). The latter was observed after ethanol stress suggesting that changes in membrane fluidity may play a role in its insertion (Horváth et al 2008).…”
Section: Hsp70mentioning
confidence: 65%